Complement Component 3 Negatively Regulates Antibody Response by Modulation of Red Blood Cell Antigen - Mener, Amanda; Arthur, Connie M.; Patel, Seema R.; Liu, Jingchun; Hendrickson, Jeanne E.; Stowell, Sean R. (Frontiers in Immunology, 2018)
Red blood cell (RBC) alloimmunization can make it difficult to procure compatible RBCs for future transfusion, directly leading to increased morbidity and mortality in transfusion-dependent patients. However, the factors that regulate RBC alloimmunization remain incompletely understood. As complement has been shown to serve as a key adjuvant in the development of antibody responses against microbes, we examined the impact of complement on RBC alloimmunization. In contrast to the impact of complement component 3 (C3) in the development of an immune response following microbial exposure, transfusion of C3 knockout (C3 KO) recipients with RBCs expressing KEL (KEL RBCs) actually resulted in an enhanced anti-KEL antibody response. The impact of C3 appeared to be specific to KEL, as transfusion of RBCs bearing another model antigen, the chimeric HOD antigen (HEL, OVA and Duffy), into C3 KO recipients failed to result in a similar increase in antibody formation. KEL RBCs experienced enhanced C3 deposition and loss of detectable target antigen over time when compared to HOD RBCs, suggesting that C3 may inhibit antibody formation by impacting the accessibility of the target KEL antigen. Loss of detectable KEL on the RBC surface did not reflect antigen masking by C3, but instead appeared to result from actual removal of the KEL antigen, as western blot analysis demonstrated complete loss of detectable KEL protein. Consistent with this, exposure of wild type B6 or C3 KO recipients to KEL RBCs with reduced levels of detectable KEL antigen resulted in a significantly reduced anti-KEL antibody response. These results suggest that C3 possesses a unique ability to actually suppress antibody formation following transfusion by reducing the availability of the target antigen on the RBC surface.